European Journal of Applied Mathematics (Cambridge [England] ; New York, NY : Cambridge University Press, 1990)
Access available online from 1997-
Title from cover.
Chemical abstracts
Absorbed: Surveys on mathematics for industry.
SERBIB/SERLOC merged record
Keywords: Mathematics -- Periodicals; Angewandte Mathematik; Zeitschrift